A yield criterion for porous crystalline materials with inner pressure. (1st October 2020) - Yu, Long; Sui, Haonan; Liu, Wenbin; Chen, Lirong; Liu, Ying; Duan, Huiling
Abstract: To theoretically analyze the effects of voids and inner pressure on the nonlinear deformation behavior of porous metallic materials, a yield criterion related to the von Mises stress and hydrostatic stress has been developed based on variational approach. Under different stress triaxial loading conditions, the proposed criterion is applied to analyze the yield surface of porous single crystal with various porosities and inner pressures. It is revealed that the existence of voids and inner pressure significantly reduces the size of yield surface for porous single crystal under high stress triaxial loading, whereas this effect is insignificant in the case of low stress triaxiality. Furthermore, by considering the effect of inner pressure on the effective shear stress of dislocation movement, a modified crystal plastic theory is adopted to evaluate the plastic deformation behavior of porous single crystal with inner pressure. Combining the self-consistent theory, the influence of voids and inner pressure on the yield strength and flow stress of polycrystalline materials have been obtained. Numerical results of proposed criterion can match well with corresponding results of the finite element simulation and experiment, indicating the good accuracy and rationality of the proposed criterion.